DESAIN KEMASAN MAKANAN KUB SUKARASA DI DESA WISATA ORGANIK SUKOREJO SRAGEN - Syamsudin, Syamsudin; Wajdi, M. Farid; Praswati, Aflit Nuryulia (Benefit, 2015)
This study analyzes the design of packaging for both food products produced by KUB Sukarasa Tourism Village Organic Sukorejo Sragen. This is important because the packaging is one of the marketing tools. Food products in KUB Sukarasa in District Sambirejo Sragen sold in transparent plastic packaging and without label. This makes the level of sales is not maximized. This research has three objectives: first, create a packaging design that has the right size so easily carried by consumers and attractive for sale by the merchant. The second objective, informative designing packaging labels, such as product name, manufacturers address, net weight, expiration date, product composition, and information about kosher. The research method used was experimental. The end result of this research is a product packaging design good food and interesting. This packaging design can be used by UMKM to develop their product marketing strategies in order to increase sales.